The Economics of Tobacco in Sri Lanka - Arunatilake, Nisha (World Bank, Washington, DC, 2013)
This paper describes trends in tobacco use in Sri Lanka, assesses the economic contribution of the industry (jobs, earnings, tax revenues and trade balance), and analyses the relationship between demand for cigarettes and prices and incomes, looking at different socioeconomic groups. It uses the estimated elasticities to simulate the likely impact of a tax increase on prices, government revenues and on demand, expenditures and tax burdens of different socio-economic groups.